Computational structural dynamics : proceedings of the International Workshop, Iziis, Skopje, Macedonia, 22-24 February 2001 /: proceedings of the International Workshop, Iziis, Skopje, Macedonia, 22-24 February 2001. (2020) - Unknown
No abstract available